2020
DOI: 10.32473/edis-hs1185-2020
|View full text |Cite
|
Sign up to set email alerts
|

Mango Postharvest Best Management Practices Manual

Abstract: Improving the quality and consistency of the fresh mangos that are available to consumers in the United States is an important goal of the National Mango Board (NMB). The NMB-funded project, Monitoring and Evaluation of the Mango Supply Chain to Improve Mango Quality (referred to hereafter as the Mango Quality Project), was conducted from December 2007 through April 2009 to identify impediments to successfully meeting that goal. The final deliverable of the Mango Quality Project is this best management practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The ‘Glenn’ and ‘Saigon’ trees were 21 years old in 2018, and the ‘Mamme’ tree was 46 years old in 2018 and had been in production since about 4 years old. The samples were shipped overnight to the Citrus Research and Education Center (Lake Alfred, FL, U.S.A.), University of Florida, and were maintained at room temperature until fully ripe based on peel color and firmness, as previously reported . The maturity of samples was confirmed by the flesh firmness test using a penetrometer with a 5 / 16 in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘Glenn’ and ‘Saigon’ trees were 21 years old in 2018, and the ‘Mamme’ tree was 46 years old in 2018 and had been in production since about 4 years old. The samples were shipped overnight to the Citrus Research and Education Center (Lake Alfred, FL, U.S.A.), University of Florida, and were maintained at room temperature until fully ripe based on peel color and firmness, as previously reported . The maturity of samples was confirmed by the flesh firmness test using a penetrometer with a 5 / 16 in.…”
Section: Methodsmentioning
confidence: 99%
“…The maturity of samples was confirmed by the flesh firmness test using a penetrometer with a 5 / 16 in. tip [criterion for the full ripe: 2–6 pounds of force (lbf)] . The total soluble solid (TSS)/acid maturity ratios were 24.41, 18.43, and 13.04 for ‘Glenn’, ‘Mamme’, and ‘Saigon’, respectively (measured in 2018 samples) .…”
Section: Methodsmentioning
confidence: 99%
“…Mango ʻAtaulfoʼ del ciclo agrícola 2019, se obtuvo en el estado de Guerrero en condición de madurez para consumo, número cinco en la escala de color de la pulpa del fruto reportada para este cultivar (Brecht et al, 2010) condición donde alcanza la calidad organoléptica óptima como fruta de mesa (NMX-FF-058-SCFI-2006). Los frutos se desinfectaron con solución de hipoclorito de sodio al 0.5 % por 3 min.…”
Section: Materiales Y Métodosunclassified
“…The literature on management practices [6][7][8] explores that while applying emerging management practices, a grounded and knowledge-based point of view is needed. Adhikari [9] suggested that all strategies and practices must be accompanied by knowledge management to gain a competitive advantage in the modern corporate world.…”
Section: Introductionmentioning
confidence: 99%